Pemberdayaan Ekonomi Pemilik Usaha Pembuatan Nata de Coco, Dusun Jragan II, Kabupaten Bantul - Herry Maridjo; Y.M.V. Mudayen; Wiwid Wijayanti (Universitas Sanata Dharma, 2018)
The purpose of the Science and Technology Implementation of Nata de Coco Business Owners is to increase the income of the Nata de Coco business owners through education and training on product processing as well as on the management of their business. The idea of implementing science and technology for Nata de Coco entrepreneurs stemmed from the fact that nata de coco entrepreneurs were generally less skilled in processing nata de coco products. The products were less hygienic and were not marketed under their own trademark. The specific target in IbM's activities was the increasing income of the nata de coco businessmen. The method used to achieve this goal was a collaborative method through various trainings, intensive facilitation, hands-on practice, monitoring and evaluation. The outcome of IbM's program was the production of nata de coco's distinctive, varied, hygienic, and delicious products so that the sales turnover and the nata de coco craftsmen income continue to increase.